Lactobacillus Plantarum for Human Life: Molecular Approach - Megahati S, Ruth Rize Paas (RADINKA JAYA UTAMA PUBLISHER, 2025)
Lactobacillus plantarum (L. plantarum) increases short-chain fatty acids (SCFA) levels in the intestines, which acts as a signal to activate the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. This activation is crucial for reducing oxidative stress and maintaining mitochondrial balance. This study aims to review several research papers that explore and highlight how L. plantarum makes SCFAs to activate Nrf2, specifically the strategies it uses to combat free radicals. The systematic review technique systematically investigates, assesses, analyzes, and interprets all study findings relevant to the research topic. We sourced articles from three databases: Scopus, Web of Science, and Google Scholar, covering the period from 2014 to 2024. The study found that SCFAs made by L. plantarum are important signals that trigger the Nrf2 signaling pathway, which helps protect cells from damage caused by oxidation and inflammation. L. plantarum is a beneficial probiotic that uses SCFAs to trigger the Nrf2 pathway, providing strong protection against free radicals and supporting various health benefits.